Patterns of usage and preferences of users for tuberculosis-related text messages and voice calls in Uganda - Ggita, Joseph M. (Int J Tuberc Lung Dis, 2018)
BACKGROUND: Little information exists about mobile-phone usage or preferences for tuberculosis-related health communications in Uganda. METHODS: We surveyed household contacts of tuberculosis patients in urban Kampala, Uganda, and clinic patients in rural central Uganda. Questions addressed phone access, usage, and preferences for TB-related communications. We collected qualitative data about messaging preferences. RESULTS: We enrolled 145 contacts and 203 clinic attendees. Most contacts (58%) and clinic attendees (75%) owned a mobile phone, while 42% of contacts and 10% of clinic attendees shared one. 94% of contacts and clinic attendees knew how to receive an SMS, but only 59% of contacts ≥45 years (vs. 96% among contacts <45 years, p=0.0001). All contacts and 99% of clinic attendees were willing and capable of receiving personal-health communications by SMS. 55% of contacts preferred detailed messages disclosing test results, while 45% contacts preferred simple messages requesting a clinic visit to disclose results. CONCLUSIONS: Most urban household tuberculosis contacts and rural clinic attendees reported access to mobile phones and a willingness to receive tuberculosis-related personal-health communications by voice call or SMS. However, frequent phone sharing and variable messaging abilities and preferences suggest a need to tailor design and monitoring of mHealth interventions to the target recipients.